Molecular Characterization of Colistin Resistance in Pseudomonas aeruginosa Isolates: Insights from a Study in Bangladesh - Mia, Izaz; Haque, Nooriya; SM, Shamsuzzaman; Atiquzzaman, Tarafder Mohammad; Fatema, Jannatun; Raihan, Muhammad (Archives of Clinical and Biomedical Research, 2025)
Background: Pseudomonas aeruginosa is a major opportunistic pathogen responsible for severe hospital-acquired infections. Increasing antimicrobial resistance, particularly to colistin, which is the last-resort therapy for multidrug-resistant (MDR) Gram-negative bacteria, poses a critical challenge. Objective: This study aimed to determine the prevalence, resistance profile, and colistin resistance genes among P. aeruginosa isolates from clinical samples. Methodology: This cross-sectional study was conducted at the Department of Microbiology and Immunology at Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh. The research was conducted over one year, from January to December 2022. A total of 330 clinical specimens were subjected to culture and sensitivity testing. PCR screened colistin-resistant isolates for pmrA, pmrB, pmrC, phoP, and phoQ genes. Results: Culture positivity was observed in 64.24% of samples, with wound swabs and pus showing the highest rate (72.41%), followed by endotracheal aspirates (70.00%). P. aeruginosa constituted 24.05% of isolates, predominantly from wound and urine samples. High resistance rates were noted for ciprofloxacin (88.23%), ceftazidime (84.31%), gentamicin (68.62%), and carbapenems (imipenem 56.86%, meropenem 60.78%). Colistin resistance was detected in 25.49% of isolates. Among these, 56.86% were MDR, 21.56% extensively drug-resistant (XDR), and 13.72% pandrugresistant (PDR). The pmrA gene was most frequent (46.15%), followed by pmrB (38.46%), pmrC and phoP (30.76% each), and phoQ (23.07%). Conclusions: The predominance of MDR and XDR P. aeruginosa underscores an urgent need for antimicrobial stewardship and surveillance. Detection of multiple regulatory genes in colistin-resistant isolates suggests complex molecular mechanisms requiring continued genomic monitoring.